Periplaneta americana Ameliorates Dextran Sulfate Sodium-Induced Ulcerative Colitis in Rats by Keap1/Nrf-2 Activation, Intestinal Barrier Function, and Gut Microbiota Regulation - Ma, Xuewei; Hu, Yichen; Li, Xin; Zheng, Xiaoting; Wang, Yitao; Zhang, Jinming; Fu, Chaomei; Geng, Funeng (Frontiers in Pharmacology, 2018)
Periplaneta americana, a magic medicinal insect being present for over 300 million years, exhibits desirable therapeutic outcome for gastrointestinal ulcer treatment. Nowadays, P. americana ethanol extract (PAE) has been shown to ameliorate ulcerative colitis (UC) by either single-use or in combination with other therapeutic agents in clinics. However, its underlying mechanisms are still seldom known. Herein, we investigated the anti-UC activity of PAE by alleviating intestinal inflammation and regulating the disturbed gut microbiota structure in dextran sulfate sodium (DSS)-induced UC rats. Based on multiple constitute analyses by HPLC for quality control, PAE was administrated to DSS-induced UC rats by oral gavage for 2 weeks. The anti-UC effect of PAE was evaluated by inflammatory cytokine production, immunohistochemical staining, and gut microbiota analysis via 16S rRNA sequencing. As a result, PAE remarkably attenuated DSS-induced UC in rats. The colonic inflammatory responses manifested as decreased colonic atrophy, intestinal histopathology scores and inflammatory cytokines. In addition, PAE improved the intestinal barrier function via activating Keap1/Nrf-2 pathway and promoting the expressions of tight junction proteins. It was observed that the UC rats showed symptoms of gut microbial disturbance, i.e., the increased Firmicutes/Bacteroidetes ratio and the significantly decreased probiotics such as Lactobacillus, Roseburia, and Pectobacterium, which were negatively correlated with these detected pro-inflammatory cytokines (secreted by immune CD4+ T cells, and including IFN-γ, TNF-α, IL-6, IL-8, IL-17, IL-1β). Besides, PAE administration regulated the abnormal intestinal microbial composition and made it similar to that in normal rats. Therefore, PAE could attenuate the DSS-induced UC in rats, by means of ameliorating intestinal inflammation, improving intestinal barrier function, and regulating the disturbed gut microbiota, especially improving beneficial intestinal flora growth, modulating the flora structure, and restoring the intestinal-immune system.